Adapting a Sexual Violence Primary Prevention Program to Ghana Utilizing the ADAPT-ITT Framework. (January 2020) - Munro-Kramer, Michelle L.; Rominski, Sarah D.; Seidu, Abdul-Aziz; Darteh, Eugene K. M.; Huhman, Anne; Stephenson, Rob
Prevention of sexual violence among young people has become a priority area in Ghana, although few initiatives have focused on this topic. The ADAPT-ITT (A ssessment, D ecisions, A dministration, P roduction, T opical experts, I ntegration, T raining staff, andT esting) framework was used to systematically adapt an evidence-based sexual violence prevention program developed in the United States to a university in Ghana. Results from cognitive interviews, focus groups, beta testing, and topical experts indicate the adapted primary prevention program is promising for use in Ghanaian universities. To our knowledge, this is the first study that has used the ADAPT-ITT framework for a sexual violence program.